Coinfection with Tritrichomonas foetus and Giardia duodenalis in Two Cats with Chronic Diarrhea - Sergio A. Zanzani; Alessia L. Gazzonis; Paola Scarpa; Emanuela Olivieri; Hans-Jörg Balzer; Maria Teresa Manfredi (Case Reports in Veterinary Medicine)
A Tritrichomonas foetus and Giardia duodenalis mixed infection was diagnosed in two Maine Coon cats aged six months. One of them presented a history of chronic liquid diarrhea and of several unsuccessful treatments. In both cats, G. duodenalis and trichomonads were detected in fecal smears from freshly voided feces; the presence of T. foetus was confirmed by a real-time PCR assay. The cats completely recovered after treatment with ronidazole. In a refrigerated fecal sample collected from the cat with chronic diarrhea, drop-shaped trichomonad pseudocysts smaller than G. duodenalis cysts were detected. They appeared brownish or light-bluish when stained with Lugol’s solution or with Giemsa stain, respectively, and their morphological features were similar to those expressed by bovine T. foetus pseudocysts in vitro. Existence of pseudocysts even in feline trichomonads is noteworthy as they could represent a form of protozoan resistance due to unfavorable conditions whose detection in refrigerated feces can be a useful clue for clinicians.